Water Quality Assessment of Al-Gharraf River, South of Iraq by the Canadian Water Quality Index (CCME WQI) - Ewaid, Salam Hussein (Iraqi Journal of Science, 2022)
Water quality of Al-Gharraf River, which considered the main branch of Tigris River south of Iraq was examined using the Canadian Council of Ministers of the Environment Water Quality Index (CCME-WQI) for aquatic life protection and irrigation. Water samples were collected monthly from five sampling stations during 2013-2014 and 17 physicochemical parameters were analyzed: Temperature, hydrogen ion concentration (pH), electrical conductivity, dissolved oxygen, turbidity, alkalinity, chloride, calcium, magnesium, sulfate, phosphate, nitrate, sodium, lead, cadmium, nickel and zinc.The model classified water of Al-Gharraf River as poor for aquatic life protection and fair for irrigation with seasonal overall WQI value of 30-39 and among stations was 38-39.